Studying the quality of the main outfall drain water in Al Qadisiyah area and its suitability for some agricultural uses / Iraq - Ali Hamid Abdullah; Fouad Manhar Alkam; Ali Waheed Abbas (University of Thi-Qar Journal of Science, 2019)
The present study was conducted for the period from November 2011 to October 2012. Three sites were identified in this study to measure some of the physical and chemical properties of the main outfall drain water, the passer Al-Qadisiyah Governorate to determine the quality of the public water, physical and chemical, and its suitability for irrigation. The results of the current study showed that the values of the air temperature ranged between (4 - 45 C°) and water (9.5-30C°). The pH values were bent to the basic side and ranged from (7.7-8.4), dissolved oxygen values (5.1-10.8) mg / l and electrical conductivity was ranged from(3380-11520) μs / cm, Salinity ranged between(2.1 -7.3g / L), where water is classified as oligohalic, The total dissolved solids values ranged between  (3310 - 7650) mg / L. The high alkalinity in the study ,  total alkalinity ranged from (1140 -2280mg CaCo3/ L), Calcium ions were recorded (131.4 -320-mg CaCo3 / L), and Magnesium (135.9-401.2 mg CaCo3/ L). The values of sodium exceeded the Iraqi and international standard limits and ranged between (708.7-1256mg/l), Potassium values ranged between (13.3 -28.2mg / L), The values of chloride were high, ranging between (849.7 -1939.3mg / L) and sulphate (734.8-1074.2) mg / l), The ratio of sodium adsorption exceeded the permissible limits for irrigation of agricultural crops according to the classification of the American salinity laboratory (1954) ranging from  (35.973.5 %). The results of the study showed that the MOD water is physically and chemically unfit for the determinants identified in this study, and that its use by cattle and poultry can cause health problems and are not suitable for irrigating crops according to the classification of the American salinity laboratory. It should be noted, however, that researchers in the current study found that some of the farmers adjacent to their land to the public post cultivated wheat and barley crops on the ground, Which leads us to question the actual salinity Borne by those crops.